1993
DOI: 10.1073/pnas.90.19.9085
|View full text |Cite
|
Sign up to set email alerts
|

The human gastrin/cholecystokinin type B receptor gene: alternative splice donor site in exon 4 generates two variant mRNAs.

Abstract: Gastrin and its carboxyl-terminal homolog cholecystokinin (CCK) exert a variety of biological actions in the brain and gastrointestinal tract that are mediated in part through one or more G protein-coupled receptors which exhibit similar affinity for both peptides. Genomic clones encoding a human gastrin/CCKB receptor were isolated by screening a human EMBL phage library with a partial-length DNA fragment which was based on the nucleotide sequence of the canine gastrin receptor. The gene contained a 1356-bp op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
38
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(39 citation statements)
references
References 27 publications
1
38
0
Order By: Relevance
“…These chimeric constructs take advantage of the fact that the genes encoding human CCK1R and CCK2R each contain fi ve exons in a similar organization ( 17,(32)(33)(34). The exons from CCK1R were sequentially replaced by exons from CCK2R, starting from the N terminus.…”
Section: Structural Basis For Differential Cholesterol Sensitivity Ofmentioning
confidence: 99%
“…These chimeric constructs take advantage of the fact that the genes encoding human CCK1R and CCK2R each contain fi ve exons in a similar organization ( 17,(32)(33)(34). The exons from CCK1R were sequentially replaced by exons from CCK2R, starting from the N terminus.…”
Section: Structural Basis For Differential Cholesterol Sensitivity Ofmentioning
confidence: 99%
“…Direct sequencing of Laghi et al the product we obtained from LoVo cells demonstrated the presence of only one of the two isoforms that are known to be generated by exon 4 alternative splicing ( Fig. 4c) (Song et al, 1993). Interestingly, this isoform corresponded with the hGARE frameshiftmutated allele and has been characterized by a (T) 7 repeat in exon 5 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, gastrin stimulation of CCK-2 receptors expressed by AR42J cells was shown in an in vitro system to reverse apoptosis induced by serum withdrawal through the induction/ activation of protein kinase BAkt (Todisco et al, 2001). A number of isoforms of the CCK-2 receptor have now been discovered (Song et al, 1993;Miyake, 1995;Ohtaki et al, 1996). These include the 'long isoform' which has, due to alternate splicing, an additional five amino acids located within the third intracellular domain (Song et al, 1993;Ohtaki et al, 1996).…”
mentioning
confidence: 99%
“…A number of isoforms of the CCK-2 receptor have now been discovered (Song et al, 1993;Miyake, 1995;Ohtaki et al, 1996). These include the 'long isoform' which has, due to alternate splicing, an additional five amino acids located within the third intracellular domain (Song et al, 1993;Ohtaki et al, 1996). Use of an alternative first exon, 1b, which remains untranslated, leads to a receptor truncated at the amino-terminus, known as the DCCK-2.…”
mentioning
confidence: 99%